Design, synthesis and biological evaluation of novel potent MDM2/p53 small-molecule inhibitors. Issue 2 (15th January 2015) - Ivanenkov, Yan A.; Vasilevski, Sergei V.; Beloglazkina, Elena K.; Kukushkin, Maksim E.; Machulkin, Alexey E.; Veselov, Mark S.; Chufarova, Nina V.; Chernyaginab, Elizaveta S.; Vanzcool, Anton S.; Zyk, Nikolay V.; Skvortsov, Dmitry A.; Khutornenko, Anastasia A.; et al.
Graphical abstract